CLIMBING AS A MEASUREMENT OF LOCOMOTION ABILITY IN THE DROSOPHILA MODEL OF FRAGILE X SYNDROME - Makevic, Vedrana; Stojkovic, Maja; Biorac, Marko; Milojevic, Sara; Capovilla, Maria; Protic, Dragana (Medical Research, 2024)
Introduction: Fragile X syndrome (FXS) is the most common monogenetic cause of Intellectual Disability (ID) and Autism Spectrum Disorder (ASD) in humans. The Drosophila melanogaster model of FXS (dFMR1 mutants) is an excellent model for research in the field of FXS. The aim of this study was a comprehensive investigation of climbing abilities, as a measurement of locomotion, in the dFMR1B55 line as a Drosophila model of FXS. Methods: In this study, w1118 and dFMR1B55 lines of fruit flies were used. The climbing performance of flies has been examined using a climbing performance assay for groups of flies as well as for individual flies. Parameters that represent climbing ability, speed and endurance have been determined. Females and males were analyzed separately. Results: This study revealed: (i) worse climbing performance of dFMR1B55 males in comparison to w1118 males; (ii) worse climbing success of dFMR1 B55 females in comparison to w1118 females; (iii) better climbing performance of top performer males in comparison to top performer females in the individual and group climbing test in both dFMR1 B55 and w1118 groups; (iv) better, but not statistically significant, climbing performance (based on the time needed for 50% of flies to complete the task) and higher success rate in dFMR1 B55 females in comparison to dFMR1 B55 males. Conclusion: According to the results of the current study, climbing impairment was proved only in dFMR1B55 males, while dFMR1B55 females had climbing abilities similar to control w1118 females.